2021
DOI: 10.3389/fmicb.2021.731770
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community and Fermentation Characteristics of Native Grass Prepared Without or With Isolated Lactic Acid Bacteria on the Mongolian Plateau

Abstract: This study aimed to isolate and identify lactic acid bacteria (LAB) from the native grass and naturally fermented silage from the Mongolian Plateau. The effect of selected strains on bacterial community and quality of native grass silage was also studied. Strains XM2, 265, and 842 could grow normally at 15°C–30°C, pH 4.0–8.0, and NaCl 3 and 6.5%; they were identified as Lactiplantibacillus plantarum subsp. plantarum, Pediococcus acidilactici, and Latilactobacillus graminis, by sequencing 16S rRNA, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 50 publications
8
27
3
Order By: Relevance
“…This study found that Proteobacteria was the most abundant phylum in FM, accounting for more than 85%, which is consistent with previous studies that Proteobacteria was the dominant phylum in fresh native grass ( You et al, 2021 ). In the present study, Firmicutes and Proteobacteria were prevalent in all treatments in our research, and the community composition altered with ensiling time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that Proteobacteria was the most abundant phylum in FM, accounting for more than 85%, which is consistent with previous studies that Proteobacteria was the dominant phylum in fresh native grass ( You et al, 2021 ). In the present study, Firmicutes and Proteobacteria were prevalent in all treatments in our research, and the community composition altered with ensiling time.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the CK group, Firmicutes increased, while Proteobacteria declined in the L and L + M groups. For maize stover and red clover silage, Xu et al (2017) and Dong et al (2019) found comparable findings, which might be explained by the higher microbial populations of L ( You et al, 2021 ). Proteobacteria have a major role in polysaccharide utilization, organic matter degradation, and carbon cycling ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The higher OTUs number and Chao1 index were observed in the HA group compared with those in the MA and LA groups. The higher OTUs and Chao1 index observed in alfalfa than that in native grass may be the main reason ( Bai et al, 2020 ; You et al, 2021 ). Significant differences were observed in the Shannon index among the three groups, suggesting that the HA group had higher community evenness than MA and LA groups.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, grazing was the most common feeding system, but in recent years, the native grass hay (bales) have partially or totally replaced grazing for the ruminants in the Mongolian Plateau [4]. Ensiling is a traditional way of animal feed and green forage preservation because it can provide green forages for animals year-round, prolonging the storage time and effectively decreasing the nutrition lost in Microorganisms 2022, 10, 1154 2 of 12 forages [5]. However, the moisture content, the water-soluble carbohydrate content, and the numbers of epiphytic lactic acid bacteria microflora were lower than the requirement, making it difficult to produce silage with high quality [5].…”
Section: Introductionmentioning
confidence: 99%